Community Forums to Address the Opioid Crisis: An Effective Grassroots Approach to Rural Community Engagement. (February 2019) - Palombi, Laura; Olivarez, Michelle; Bennett, Laura; Hawthorne, Amanda N
Purpose: With opioid overdose deaths on the rise in rural Minnesota and across the nation, the call for community-based grassroots efforts is stronger than ever. Recognizing that substance use prevention and recovery programming rely upon community resources, collaborative teams planned and implemented a series of nine community forums focused on opioid and heroin use across rural northeast Minnesota to educate and unite invested community members on the critical public health issue. This article examines the outcomes of the forums and the ingredients of a successful forum. Methods: Surveys were distributed at seven rural community forums to assess measures of growth in knowledge and awareness, as well as demographic characteristics of respondents. Findings: Forums planned by university faculty and community members were effective in increasing overall awareness and knowledge of the opioid crisis within each community. Forums that were rated more highly by attendees included speakers from varied professional backgrounds and integrated cultural strengths. Communities that planned forums together have reported increased collaboration to prevent and address substance use and increased community member engagement on local grassroots coalitions since the time of the forum. Conclusions: Community forums have functioned as an effective grassroots approach to engaging rural community members in opioid use prevention and intervention efforts.